Cambridge companion to William Carlos Williams - MacGowan, Christopher J. (Cambridge companions to literature, 2016)
"This Companion contains thirteen new essays from leading international experts on William Carlos Williams, covering his major poetry and prose works - including Paterson, In the American Grain, and the Stecher trilogy. It addresses central issues of recent Williams scholarship and discusses a wide variety of topics: Williams and the visual arts, Williams and medicine, Williams's version of local modernism, Williams and gender, Williams and multiculturalism, and more. Authors examine Williams's relationships with figures such as Ezra Pound, Wallace Stevens, and H. D. and Marianne Moore, and illustrate the importance of his legacy for Allen Ginsberg, Amiri Baraka, Robert Creeley, Robert Lowell, and numerous contemporary poets. Featuring a chronology and an up-to-date bibliography of the writer, The Cambridge Companion to William Carlos Williams is an invaluable guide for students of this influential literary figure"--